2023
DOI: 10.1017/s0261444822000490
|View full text |Cite
|
Sign up to set email alerts
|

Publishing in predatory language and linguistics journals: Authors’ experiences and motivations

Abstract: This study examines the experiences and motivations of language and linguistics academics who have published in potential predatory journals (PPJs). A questionnaire was administered to 2,793 academics with publications in 63 language and linguistics PPJs, and 213 of them returned their responses. A subsample of the respondents (n = 21) also contributed qualitative data through semi-structured interviews or email responses to open-ended questions. Analyses of the survey data found that the authors were mainly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…As for the review period, 16 journals made their decision in less than 2 weeks with only two rejections proffered. Although speed of turnaround is the most prevalent reason given by researchers for promoting their research in predatory journals (Nejadghanbar et al, 2023), this shows little concern for the research process and immediately calls into question the entire review process (Shen & Björk, 2015). Further evidence for this assumption is that the entire process seemed somewhat vague and in many cases completely opaque as it was difficult to ascertain whether or not a thorough review had even been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the review period, 16 journals made their decision in less than 2 weeks with only two rejections proffered. Although speed of turnaround is the most prevalent reason given by researchers for promoting their research in predatory journals (Nejadghanbar et al, 2023), this shows little concern for the research process and immediately calls into question the entire review process (Shen & Björk, 2015). Further evidence for this assumption is that the entire process seemed somewhat vague and in many cases completely opaque as it was difficult to ascertain whether or not a thorough review had even been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our research has identified inexcusable practices by various journals; however, it needs to be pointed out that there is another side to this coin—namely that if researchers knowingly support suspect journals, the problems will continue. Unfortunately, there is widespread evidence that researchers are still being taken for a ride by predatory journals on a grand scale, and that is truly regrettable (Nejadghanbar et al, 2023). On the other hand, we can say with confidence that many of these journals flourish (at least for a season) solely on the basis of offering a relatively pain‐free avenue to achieving publication, with the promise of a rapid turn‐around without a real vetting process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations